Late onset of dropped head syndrome following mantle radiation therapy for Hodgkin lymphoma. Issue 1 (14th December 2018) - Di Stefano, Vincenzo; Attanasi, Carmine; Ferrante, Camilla; Di Muzio, Antonio
Abstract : Dropped head syndrome (DHS) is a rare condition, characterised by weakness of the cervical paraspinal muscles with sagging of the head. It is usually seen in association with neurological disorders and rarely can follow radiotherapy. We report a case of a 54-year-old man survivor of Hodgkin lymphoma (HL), who developed DHS 28 years after radiotherapy. He was referred to our department due to progressive weakness and atrophy of cervical paraspinal and shoulder girdle musculature. Physical and neurophysiological examination, electromyography and MRI confirmed the diagnosis of DHS. In the following years, there was no progression of symptoms.